Application of robust controller in large induction motor for mitigating voltage sags - Hedayati, Mahdi (2012)
This research presents a new study on H oo robust controller based on loop shaping procedure for a static synchronous compensator (STATCOM) installed at terminals of the large induction motor. The space vector pulse width modulation (SVPWM) drive system is one of the most significant apparatus in industrial application of induction motors that utilization of this equipment is considered in this thesis and compared with static var compensator (SVC) installed at terminals of motor. It is shown that the dynamic behaviour and performance of SVC is better than SVPWM drive system for starting of the induction motor, so the time for motor speeding up is slower with lower transients, while the variations of induction motor current are in the sufficient range. A comparison between proportional-integral (PI) controllers of different shunt flexible alternating current transmission systems (FACTS) shows that STATCOM is more effective and has a better dynamic performance than SVC, so the parameters of peak time and voltage sag by using the STATCOM for starting of large induction motor without and with load are significantly decreased. The results from simulations prove that STATCOM is significantly proficient to ensure good power quality and more effective than SVC for decreasing transients, voltage profile improvement and getting better dynamic behavior of motor‟s rotor speed while symmetrical and unsymmetrical voltage sags are considered. Whereas FACTS devices have nonlinearity nature; using the conventional PI control theory with system linearization around nominal point is not a suitable method,besides, there exists the uncertainty in the system. So developed robust control theory that covers stability and performance criteria under all system uncertainties, has been applied for the controller design in power system to assure fast and stable regulation under wide range of operating circumstances. Among the different robust methods used to design the controller of shunt FACTS,H oo loop shaping procedure is known to be one of the effective and feasible control methods. So this method is considered to simulate robust controller for STATCOM installed at terminals of the large induction motor. The dynamic behaviors of induction motor are analyzed while the uncertainty of system parameters, STATCOM parameters and external disturbances are considered. Besides, in all previous research works, a robust control design using H oo loop shaping method through Graphical Loop Shaping (GLS) technique or Normalized Coprime Factorization (NCF) approach is proposed. In this thesis, both mentioned methods have been considered in the design of robust controller and have been compared together and with conventional PI controller. It is clearly observed that the output response of robust controllers using GLS and NCF methods are similar and surely have better dynamic performances than PI controller. A development has been determined that GLS method is more robust than NCF against variations of system parameters and STATCOM parameters. PI controller is not very strong against changing of system parameters and STATCOM parameters when compare with GLS and NCF methods, even the system goes to instability for a certain operating point. Another development will be presented when these H oo robust controllers and conventional PI controller are tested for external disturbances consist of a load disturbance and a sinusoidal disturbance on system performance. The results of simulations prove that all controllers are able to damp these disturbances, but both GLS and NCF methods are more robust than PI controllers to remove these perturbations. It is obviously shown that GLS method has better dynamic performance than NCF method to reject the disturbances and stronger than NCF method against load disturbance and sinusoidal disturbance uncertainties. Finally, for validation of the designed systems, this research is compared with other works. It is concluded that results of the designed controllers for SVC and STATCOM having parameters and specifications of other research works are similar with the simulation results of the mentioned work.